Service investment for online retailers with social media—Does it pay off?. (October 2018) - Hou, Ruiqi; de Koster, René; Yu, Yugang
Highlights: We model investment policies for online retailers with social network. We find optimal investment cost, profit and market share in Nash and Stackelberg markets. Social network leads to faster convergence of the market and impacts the profits and market share. We explain why leaders try to keep the lead in service investment in Stackelberg competition. Abstract: We investigate the impact of investments in delivery service with one or two major competing online retailers. Customers diffuse among the retailers, based on purchasing experience and online reviews (i.e., social network). Firms decide on investments aimed at maximizing profit. For both Nash and Stackelberg competition cases, the effect on market share, optimal investment cost and profit are calculated. Cases without social network are also studied, showing that a social network leads to faster convergence of the market. When a social network exists, both the leader and follower invest more, with higher profits. Our results confirm experiences from competition practice.